Foundations of Aural Rehabilitation : children, adults, and their families. - Tye-Murray, Nancy ([S.l.] : PLURAL PUBLISHING INC, 2022)
'Thoroughly updated with three new chapters, Foundations of Aural Rehabilitation: Adults, Children, and Their Family Members, Sixth Edition introduces the fundamentals of audiologic rehabilitation and hearing-related speech-language pathology in an easy-to-read, concise resource for the field of communication sciences and disorders. The text offers creative coverage of theory, clinical practice, and research-based approaches for identifying, diagnosing, and treating hearing-related communication disorders in children and adults. The book includes case studies, and general demographic, medical, and pop-cultural trends are considered in parallel with corresponding developments in aural rehabilitation'--
WorldCat record variable field(s) change: 050, 082, 650
Keywords: Hearing impaired -- Rehabilitation; Deaf -- Rehabilitation; Hearing impaired children -- Rehabilitation; Audiology